Hubungan Peran Perawat sebagai Edukator dengan Pemenuhan Kebutuhan Rasa Aman Nyaman Pasien - Akhmad Fahriyyan; Dyah Wiji Puspita Sari; Retno Issroviatiningrum (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Nurses have a very important role as educators in meeting basic human needs. One of them is that nurses act as educators in fulfilling the patient's sense of security and comfort. The patient's need for security and comfort is very important because it affects the length of treatment. The impact if the patient's need for safety and comfort is not met is that the patient results in injury. The aim of this research is to determine the relationship between the role of nurses as educators and fulfilling the patient's need for security and comfort in the inpatient room at Sultan Agung Islamic Hospital. This research uses a quantitative approach with a cross sectional design. A total of 132 respondents participated in this research, the sampling technique used was total sampling. The analysis used is the Chi Square test. This research reveals a significant relationship between the role of nurses as educators and fulfilling patients' needs for safety and comfort in the RSI Sultan Agung inpatient room. This relationship is indicated by a p-value of 0.000, which shows a positive direction of the relationship.. Suggestions for future researchers to expand the scope of research by involving more educational institutions and hospitals in order to obtain more generalizable results.